Essentials of nursing research : appraising evidence for nursing practice - Polit, Denise F.; Beck, Cheryl Tatano (Lippincott Williams & Wilkins, 2014)
A guide for student learning ancillaries, and instructor teaching materials which present a learning-teaching package that is designed to teach students how to read and critique research reports, and to appreciate the application of research findings to nursing practice